Thermoelectrics: A Nanostructuring Method to Decouple Electrical and Thermal Transport through the Formation of Electrically Triggered Conductive Nanofilaments (Adv. Mater. 28/2018). Issue 28 (9th July 2018) - Durán Retamal, José Ramón; Kang, Chen‐Fang; Lien, Der‐Hsien; Kuo, Wei‐Cheng; Juang, Zhen‐Yu; Tsai, Meng‐Lin; Ho, Chih‐Hsiang; Juang, Jenh‐Yih; Hsiao, Vincent K. S.; Chu, Ying‐Hao; Li, Lain‐Jong; Wu, Yue; et al.
Abstract : In article number1705385, Jr‐Hau He and co‐workers propose an innovative strategy to switch thermoelectric properties between two states without further material modification and manufacturing process by forming/disrupting electrically triggered conductive nanofilaments within semiconducting thin films. This process can controllably adjust the degree of decoupling, providing a potential resolution and performance adjustability for heat/coldness control or reduction of power consumption on demand.